Are we teaching health science students in the United States what they need to know about death and dying coping strategies? - Case, Randy D.; Judie, Erica; Kurszewski, Tammy; Brodie, Wenica; Bethel, Pollyann (Journal of Educational Evaluation for Health Professions, 2021)
Purpose: This investigation aimed to answer the following questions: are health science students provided with death and dying education before attending clinical rotations, and if so, do the students receiving this type of education perceive it as effective? Methods: In this descriptive cross-sectional survey, 96 Midwestern State University health science students were surveyed to determine the percentage of students who had received death and dying education before clinical rotations, as well as the students' perception of educational effectiveness for those who had received end-of-life training. A self-report questionnaire presented nursing, radiologic sciences, and respiratory care students with a series of questions pertaining to the education they had received concerning the death and dying process of patients. Results: Of the 93 students who had already started their clinical rotations, 55 stated they had not received death and dying education before starting clinical courses. Of the 38 who had received death and dying education, only 17 students believed the training was effective. Conclusion: It is imperative that health science educational programs implement death and dying education and training into the curriculum, and that criteria for evaluating effectiveness be an essential part of death and dying education and training in order to ensure effectiveness.